Atomically Thin 2D Interfaces as Sensors for Molecular Permeability through Cellular Layers and Thin Tissues. (12th January 2022) - Koman, Volodymyr B.; Gong, Xun; Bakh, Naveed A.; Silmore, Kevin; Salem, Daniel P.; Lew, Tedrick Thomas Salim; Kuehne, Matthias; Kozawa, Daichi; Park, Minkyung; Strano, Michael S.
Abstract: The permeability of cell layers plays a critical role in the life sciences and medicine. It remains a long‐standing challenge to assess molecular transport through cell layers with subcellular spatial resolution. Herein, a novel sensing platform employing atomically thin and photoluminescent MoS2 monolayers as 2D sensing interfaces is developed to detect the diffusion of probe molecules through cellular layers and tissues. The 2D form factor enables monolayer MoS2 to serve as an array of 20 164 optical sensors covering a total area of 420 × 420 µm 2, being the only nanosensor interface that can spatially image molecular permeability in this way. In a single layer of human umbilical vein endothelial cells (HUVEC), regions with diffusivities ranging from 1 × 10 −9 to 3 × 10 −8 cm 2 s −1 are found that are in part spatially correlated with the immunofluorescence of vascular endothelial (VE)‐cadherin proteins found on the cell membrane. However, the new technique clearly identifies these locations as breaks of nanoscale cellular junctions less than 40 nm in length in intercellular clefts that are otherwise impossible to measure with conventional microscopy. With the ability to measure permeability through various tissues, this 2D sensing interface allows the measurement of biological properties to assist the development of targeted therapeutics and mechanistic models. Abstract : Employing atomically thin and photoluminescent MoS2 monolayers, a novel 2D sensing interface is developed to detect the diffusion of probe molecules through cellular layers and tissues. In a single cellular layer, breaks of nanoscale cellular junctions less than 40 nm in length are identified that are otherwise impossible to measure with conventional microscopy.